MEDULLARY THYROID CARCINOMA DISCOVERED THROUGH ELEVATED CEA IN THE COURSE OF HEALTH SCREENING – A REPORT OF 10 CASES - Tan, Khai Tong; Tan, Joshua Zhi Chien (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION 10 cases of sporadic Medullary Thyroid Carcinoma were seen where their initial presentation was asymptomatic elevation of CEA level discovered on health screening. CASE 6 men and 4 women (ages 36 to 68 years) were found to have elevated CEA levels (2 former smokers). The time between detection of elevated CEA to time of final diagnosis ranged from 2 months to 9 years. Significantly 3 patients had CEA elevation for 8, 8 and 9 years respectively before diagnosis. At diagnosis, 9 patients appeared to have limited disease (confined to the thyroid) in spite of the long duration of CEA elevation. One patient was noted to have lymph node metastases (diagnosed 4 months). This patient had persistent Calcitonin elevation and had a second operation later. CONCLUSION The long duration of asymptomatic presentation suggested that these incidental tumours may not be clinically significant. However one of the patients who was diagnosed only 8 years after initial CEA elevation, showed on followup, persistent elevation of Calcitonin (which doubled within 24 months). Lymph node recurrence was noted. After a second surgery, her Calcitonin remained above 400 ng/L. Four other patients had persistently elevated Calcitonin post-operation. Only 4 had normalisation of Calcitonin levels on follow-up (2 to 10 years). The 10 patients appeared to have innocuous presentation initially but on follow up had a variable outcome. Some may have significant longterm disease.